2010
DOI: 10.1038/jid.2010.29
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Irradiation Induces CYR61/CCN1, a Mediator of Collagen Homeostasis, through Activation of Transcription Factor AP-1 in Human Skin Fibroblasts

Abstract: UV irradiation from the sun elevates the production of collagen-degrading matrix metalloproteinases (MMPs) and reduces the production of new collagen. This imbalance of collagen homeostasis impairs the structure and function of the dermal collagenous extracellular matrix (ECM), thereby promoting premature skin aging (photoaging). We report here that aberrant dermal collagen homeostasis in UV-irradiated human skin is mediated in part by a CCN-family member, cysteine-rich protein-61 (CYR61/CCN1). CYR61 is signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
85
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 57 publications
6
85
0
Order By: Relevance
“…CCN1 is also significantly induced by acute UV irradiation in human skin in vivo, and in UV-irradiated human dermal fibroblasts in vitro [77,78]. CCN1 functions as a key mediator of UV-induced aberrant collagen homeostasis.…”
Section: Ccn1 Functions As a Critical Mediator Of Oxidative Stress-inmentioning
confidence: 99%
See 2 more Smart Citations
“…CCN1 is also significantly induced by acute UV irradiation in human skin in vivo, and in UV-irradiated human dermal fibroblasts in vitro [77,78]. CCN1 functions as a key mediator of UV-induced aberrant collagen homeostasis.…”
Section: Ccn1 Functions As a Critical Mediator Of Oxidative Stress-inmentioning
confidence: 99%
“…In human skin, CCN1 is predominantly expressed in dermal fibroblasts [38], and significantly elevated in dermal fibroblasts in aged human skin in vivo [38,39,77]. In cultured human dermal fibroblasts, the elevated expression of CCN1 not only inhibits the expression of type I procollagen, but also concurrently increases the expression of multiple MMPs and cytokines [36,38,39,77].…”
Section: Ccn1 Functions As a Critical Mediator Of Oxidative Stress-inmentioning
confidence: 99%
See 1 more Smart Citation
“…In cell culture models, CCN1 recombinant protein regulates cell adhesion, cell migration, cell-matrix interactions, and the synthesis of extracellular matrix (24 -26). Furthermore, elevated CCN1 up-regulates MMP-1 protein expression in cultured primary human skin dermal fibroblasts (22,23).…”
mentioning
confidence: 99%
“…CCN proteins play fundamental roles in growth, differentiation, angiogenesis, migration, and extracellular matrix regulation (19,21). We previously reported that CCN1 is expressed in human skin dermis and is substantially elevated in the dermis of naturally aged, photoaged, and acutely UV-irradiated human skin (22,23). In cell culture models, CCN1 recombinant protein regulates cell adhesion, cell migration, cell-matrix interactions, and the synthesis of extracellular matrix (24 -26).…”
mentioning
confidence: 99%